PESAN DAKWAH DALAM TAYANGAN MUSLIM TRAVELERS DI NEWS AND ENTERTAINMENT TELEVISION (NET.) EPISODE KISAH DIBALIK TEMBOK PEMBATAS DI TEPI BARAT PALESTINA - Ferdiansah, Farabi; Marini (Universitas Muhammadiyah Kotabumi, 2023)
Islam is a blessing for the universe. It is not surprising that in practice, conveying information about the spread of Islam throughout the earth is an interesting thing to discuss. Why not, through news written about the spread of Islam throughout the world, people will know about how Islam grows and develops in a country. The method in this research uses qualitative analysis. This research uses a qualitative method with Roland Barthes' semiotic analysis. Barthes explained that the key to meaning analysis is denotation, connotation and myth. The results of this research are that the message of da'wah can be seen from Muslim tourist broadcasts in several scenes of broadcasts that contain da'wah messages